„Ucieczki” młodzieży w „Nowe Światy” - Walancik, Marek (Studia Edukacyjne, 2019)
Undoubtedly, we have time when, as a result of the dizzying pace, young people grow up in “bizarre cultural patterns”. In the author’s opinion, modern youth are growing up in the space of eccentric signposts that lead to escape in the so-called “New Worlds”. Based on the results of empirical research on experimenting with drugs, psychoactive substances and other risky behaviors, it indicates the causes and effects of escaping in the so-called “New Worlds”.